Electronic commerce and the role of the WTO - Marc Bacchetta; Patrick Low; Aaditya Mattoo; Ludger Schuknecht; Hannu Wager; Madelon Wehrens (World Trade Organization (WTO), 1998)
The study was written as a means of providing background information for the 132 WTO members who are now developing policy responses to this new form of commerce. Written by a team of economists from the WTO Secretariat, it identifies the complexities as well as the potential benefits of trade via the Internet. The book describes the extraordinary expansion of opportunities that electronic commerce offers, including for developing countries.
Keywords: 330